2015
DOI: 10.1159/000431223
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in Placental Magnetic Resonance Imaging Relaxation Parameter in Murine Pregnancy: Compartmental Analysis

Abstract: Objective: To quantify gestation-dependent longitudinal changes in the magnetic resonance transverse relaxation time (T2) parameter of the major constituent regions of the mouse placenta and to evaluate their relative contributions to changes in overall placental T2. Methods: Timed-pregnant CD-1 mice underwent magnetic resonance imaging at 7.0 T field strength, on gestational day 13 (GD13), GD15 and GD17. T2 of the placenta and its constituent high and low blood perfusion regions were quantified. A linear mixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 62 publications
(77 reference statements)
2
3
0
Order By: Relevance
“…In normal pregnancies, we found a negative linear correlation between placental T2 and GA at the time of MRI. This finding is in accordance with the majority of previous human studies 12,18,[22][23][24] and murine models. 22,23 The negative correlation between placental T2 and gestational age at MRI may be explained by normal morphological changes evolving during gestation such as increasing villous density and fibrin deposition 12 as well as decreasing placental oxygenation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In normal pregnancies, we found a negative linear correlation between placental T2 and GA at the time of MRI. This finding is in accordance with the majority of previous human studies 12,18,[22][23][24] and murine models. 22,23 The negative correlation between placental T2 and gestational age at MRI may be explained by normal morphological changes evolving during gestation such as increasing villous density and fibrin deposition 12 as well as decreasing placental oxygenation.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in accordance with the majority of previous human studies 12,18,[22][23][24] and murine models. 22,23 The negative correlation between placental T2 and gestational age at MRI may be explained by normal morphological changes evolving during gestation such as increasing villous density and fibrin deposition 12 as well as decreasing placental oxygenation. 25 This finding is highly important, as it underlines that any comparison of placental T2 between groups needs to be adjusted for differences in gestational age at MRI.…”
Section: Discussionsupporting
confidence: 93%
“…A significant difference in fractional blood volume was revealed (53.0% for the L-NAME group vs. 46.7% for controls; p < 0.01), whereas placental perfusion was found to be not significantly different in the two groups (140 mL/min/100 mL in the L-NAME group vs. 149 mL/min/100 mL in controls; p = 0.49). This kind of modification was suggested by Krishnamurthy et al [24] during gestation. They showed that T2 was smaller in the lowest perfused zone compared to the highest perfused zone, while there was no difference in their decrease rate relative to that of the whole placenta.…”
Section: Discussionmentioning
confidence: 71%
“…Deoxyhemoglobin yields lower T2* values and thus reflects blood and oxygen supply to the organ 7 . Although ultrasound and T2* mapping are useful for imaging the human placenta, these methods yield measures that are averaged over the entire placenta or a region of interest containing various placental compartments and cell types 8 , 9 , 10 , 11 , 12 , 13 , resulting in reduced imaging specificity and contradictory findings 14 , 15 . Considering the heterogeneous composition of the human placenta, quantifying oxygenation levels separately for individual placental compartments holds great promise to improve the characterization of human placental development and disease mechanism.…”
Section: Introductionmentioning
confidence: 99%